1991
DOI: 10.1177/39.10.1940307
|View full text |Cite
|
Sign up to set email alerts
|

Immunoelectron microscopic evidence for organ differences in the composition of peroxisome-specific membrane polypeptides among three rat organs: liver, kidney, and small intestine.

Abstract: We examined the distribution ofperoxisome-specific membrane polypeptides (PMPs) among peroxisomes ofthe liver, renal cortex, and jejunal mucosa, using antibodies for 70 KD, 26 KD and, 22 KD PMPs. Immunoblot analysis showed signals for 70 KD polypeptide in all three kinds of tissue, but for the other two only in the liver and renal cortex, with neither being detected in jejunal mucosa. The total amounts ofPMPs inaeased in all three organs with DEHP (di-(2-ethylhexyl)phthalate) administration. By immunoelectron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In addition to the differences in the composition of the peroxisomal matrix among tissues, Usuda et al (1991b) showed that the relative abundance of the membrane proteins differs among different rat organs.…”
Section: Introductionmentioning
confidence: 97%
“…In addition to the differences in the composition of the peroxisomal matrix among tissues, Usuda et al (1991b) showed that the relative abundance of the membrane proteins differs among different rat organs.…”
Section: Introductionmentioning
confidence: 97%
“…However, the trial was not carried out at that time. We later developed immunostaining of peroxisomal enzymes by protein A-colloidal gold complex technique using cryo-fixation and freeze-substitution embedding for electron microscopy in correlation with the intracellular localization of peroxisome proliferators [82][83][84][85][86][87][88][89][90] [82][83][84][85][86][87][88][89][90]. The results demonstrated that the peroxisome of rat hepatocyte is a spherical organelle with a single limiting membrane, containing a homogeneous matrix and a high electron dense core.…”
Section: Gold Particles In Colloidal Gold Immunostaining (Au)mentioning
confidence: 99%
“…The peroxisomal matrix of rat hepatocytes can be divided into two subcompartments, the electron-lucent subcompartment and the electron-dense subcompartment [88]. The peroxisomal membrane contains 70 kDa, 41 kDa, 26 kDa, and 22 kDa PMPs [82,85,87,90]. The matrix of hepatic peroxisomes contains catalase (Fig.…”
Section: Gold Particles In Colloidal Gold Immunostaining (Au)mentioning
confidence: 99%
See 2 more Smart Citations